Influence of institutional factors on the performance of the agricultural sector in Mozambique - Jo\~ao Z. Carrilho; Rui N. Ribeiro (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
This paper is a review of the institutions and the performance of the agricultural sector in Mozambique, using an analysis table adapted to the assessment of the connections between the institutions and economic development. In the first part, information is presented on the performance of the sector between 2008 and 2017, showing a per capita reduction in productivity and the production of foodstuffs. The second part offers an analysis on the extent to which, and the way that, the development of the sector institutions influenced agricultural performance during that period. There was found to have been institutional instability that affected performance in the sector, which was unable to slow the reduction in production and productivity, which could reflect a wider socioeconomic and institutional environment, i.e. beyond the agricultural sector. The third part looks at some elements for reflection on institutional issues that could contribute to the debate on the future development of the agricultural sector. We refer to the need to think about the future of agriculture in Mozambique from a long-term perspective, focusing on the adoption and stabilization of an institutional framework aimed at increasing agricultural productivity and preserving the environment.
Keywords: Q01; Q15; Q16; Q18; 330; agriculture; environment; institutions; agricultural policy; productivity